Lucia Jig - temporomandibular dysfunction promotes muscle relaxation? - Pereira, Cintia Piccolo; Palinkas, Marcelo; de Vasconcelos, Paulo Batista; Rancan, Sandra Valéria; Regalo, Simone Cecilio Hallak; Bataglion, César (Acta Scientiarum. Health Sciences, 2016)
Assess whether the Lucia Jig is a device that promotes masticatory muscle relaxation in individuals with temporomandibular dysfunction. This study was carried out in three stages (interviews, clinical examination, and laboratory) and participation of adult individuals, between 21 and 40 years of age, of both genders, who replied to the RDC/TMD questionnaire to diagnose muscular temporomandibular dysfunction. The Lucia Jig was prepared and electromyographic examination of the masseter and temporal muscles was performed bilaterally, in the postural condition of the mandibular at rest, after immediately installing the Lucia Jig in the oral cavity and at periods of 5, 10, 15, 20, and 30 min. The values obtained were compared using repeated measures (p < 0.05) over the entire duration of the experiment (0 to 30 min) with the Lucia Jig. There was an increase in the normalized electromyographic signal of the masticatory muscles, with the use of the Lucia Jig over the period of 30 min, with no statistically significant difference. Based on the results of this study through electromyographic data, the device did not promote masticatory muscle relaxation in individuals with muscular temporomandibular dysfunction.